Evaluation of risk of tanning addiction in a selected population of women aged 15-30 - Stawczyk, Marta; Łakis, Agnieszka; Ulatowska, Anna; Szczerkowska-Dobosz, Aneta (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Excessive exposure to natural and artificial sources of ultraviolet radiation may lead to skin cancer, skin photoaging, as well as tanning addiction. Objective . To evaluate sunbathing habits and risk of tanning addiction in a selected population of women. Material and methods. 496 women aged 15 to 30 years, studying at schools and universities with medical faculties and similar. On-line or direct anonymous answers to questionnaire, which included questions about tanning preferences, knowledge about the danger of ultraviolet radiation exposure, use of sunscreens, familial incidence of skin cancer and mCAGE questionnaire evaluating risk of tanning addiction. Results . 83.9% of respondents declared that they regularly tan. Among this group 18% had a positive result in the mCAGE questionnaire. The most popular way of getting a tan was sunbathing (70.4%), but 62.7% of women had used a sunbed at least once in a lifetime and 26.6% did so regularly. The respondents using sunbeds were most often (20.2%) cosmetology students. A statistically significant correlation between duration of sunbed session and a positive result in the mCAGE questionnaire was observed. The biggest group of women (38%) that declared they had never used a sunbed consisted of secondary school students. Conclusions . According to the results of our study, using natural and artificial sources of ultraviolet radiation is still popular among young women. This population is also at risk of tanning addiction. Therefore widespread educational programmes concerning health consequences of excessive exposure to ultraviolet radiation are essential.